Surgical treatment options following chemotherapy plus cetuximab or bevacizumab in metastatic colorectal cancer—central evaluation of FIRE-3. (January 2018) - Modest, D.P.; Denecke, T.; Pratschke, J.; Ricard, I.; Lang, H.; Bemelmans, M.; Becker, T.; Rentsch, M.; Seehofer, D.; Bruns, C.J.; Gebauer, B.; Modest, H.I.; et al.
Abstract: Background: The FIRE-3 trial investigated combination chemotherapy plus either cetuximab or bevacizumab in patients with untreated metastatic colorectal cancer (mCRC) not scheduled for upfront surgery. We aimed to determine the number of patients who present with potentially resectable disease during systemic first-line therapy and to compare the findings with study reports concerning resections and outcome. Patients and methods: This evaluation of 448 patients was performed as central review blinded for treatment, other reviewers' evaluations and conducted interventions. Resectability was defined if at least 50% of the reviewers recommended surgical-based intervention. Overall survival was assessed by Kaplan–Meier method. Results: Resectability increased from 22% (97/448) at baseline before treatment to 53% (238/448) at best response ( P  < 0.001), compared with an actual secondary resection rate for metastases of 16% (72/448). At baseline (23% versus 20%) and best response (53% versus 53%), potential resectability of metastases in this molecular unselected population was similar in cetuximab-treated patients versus bevacizumab-treated patients and not limited to patients with one-organ disease. The actual resection rate of metastases was significantly associated with treatment setting ( P  = 0.02; university hospital versus hospital/practice). Overall survival was 51.3 months (95% confidence interval [CI] 35.9–66.7) in patients with resectable disease who received surgery, 30.8 months (95% CI 26.6–34.9) in patients with resectable disease without surgery and 18.6 months (95% CI 15.8–21.3) in patients with unresectable disease ( P  < 0.001). Conclusions: Our findings illustrate the potential for conversion to resectability in mCRC, certain reluctance towards metastatic resections in clinical practice and the need for pre-planned and continuous evaluation for metastatic resection in high-volume centres. ClinicalTrials.gov-identifier: NCT00433927. Highlights: We report a central review for resectability of 448 patients with metastatic colorectal cancer receiving first-line therapy (FIRE-3 trial). Twenty-two percent of the patients before systemic therapy and 53% of the patients at best response were considered candidates for resection. Actual reported resectability was 16% in the evaluated cohort. Actual resection rates were significantly associated with treatment context (university hospital versus other hospitals/practices).